ANTIOXIDANT ACTIVITY, PHENOLIC COMPOUNDS AND SENSORY EVALUATION OF INFUSION FORMULATIONS BASED ON SANKY (Corryocactus brevistylus) PEEL AND CINNAMON (Cinnamomum verum) - Contreras López, Eliana (2022)
Infusions are beverages made from herbs and other plant materials, considered healthy due to the presence of bioactive compounds. The objective of the present study was to evaluat  the antioxidant activity, phenolic compounds and sensory evaluation of infusion formulations based on sanky peel and cinnamon. The treatments studied included 100% sanky peel (INF100), 70% sanky peel +30% cinnamon (INF70) and 50% sanky peel +50% cinnamon(INF50). Phenolic content and antioxidant activity varied significantly (p < 0.05). Total phenol content was 1040; 3616 and 5353 μg GAE g-1 for INF100, INF70 and INF50 treatments, respectively. DPPH scavenging activity was 1116.67; 1647.33 and 2017.00 μg TEAC g-1 and ABTS scavenging activity was 2090; 8920 and 13425μg TEAC g-1 for INF100, INF70 and INF50 treatments respectively. The results showed that the formulations excelled in their protein, fat, ash and fiber contents. Regarding the sensory acceptability of the infusions, there were no significant differences (p > 0.05) among the three treatments, highlighting that the sensory scores were acceptable.